Chapter Lothar's manuscripts, manuscripts for Lothar, manuscripts of Lothar's time - PANI, Laura (Reti Medievali E-Book, 2022)
This paper aims to give an account of some of the manuscripts related to Lothar. In its first section an attempt is made at retracing a set of books that could have belonged to Lothar's library, nowadays known only from secondary sources. In the second section some display codices are discussed, either commissioned by Lothar, or dedicated to him, such as Lothar's Gospel Book MS Par. lat. 266 or those traditionally referred to as the «Lothar-Gruppe», whose actual connection both to Lothar and to each other is questioned here. The third and last part of the paper contains some considerations on the manuscripts produced during the years of Lothar's government in Italy, that essentially coincide with the second quarter of the ninth century.